Avian Pasteurellosis In A Male Goose - Reetha, T. Lurthu; Thomas, K. Shibi; Babu, M.; Premavalli , K. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
Avian Pasteurellosis is a contagious bacterial disease of domesticated and wild avian species caused by Pasteurella multocida. It is the most common disease affecting wild waterfowls and cause significant morbidity and mortality of migrating waterfowl (Stout and cornwen, 1976). Very little is known about the source of this infectious disease and its transmission (Botzler, 1991: Wobeser, 1992). Common synonyms of Avian Pasteurellosis are Fowl cholera and Avian haemorrhagic septicaemia. Turkeys are particularly sensitive, with mortality ranging to 65%. The recognition of this pathological condition is of ever increasing importance for differential diagnosis with avian influenza.